1977
DOI: 10.1073/pnas.74.2.789
|View full text |Cite
|
Sign up to set email alerts
|

A new class of murine leukemia virus associated with development of spontaneous lymphomas.

Abstract: A new type of murine leukemia virus has been detected in thymuses of eukemic and late preleukemic AKR mice, in lymphomas developing in NIH Swiss mice carrying the AKR ecotropic virus-inducing loci Akv-1 or Akv-2, and in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
462
0
1

Year Published

1980
1980
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 604 publications
(471 citation statements)
references
References 23 publications
8
462
0
1
Order By: Relevance
“…MCF viruses were isolated from mice by plating mitomycin Ctreated lymphoid cells as infectious centers onto mink lung (ATCC CCL-64) or SC-1 (16) cells as described previously (9). The viruses were adapted to cell-free passage in mink lung cell cultures and were carried through two cycles of limiting dilution purification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MCF viruses were isolated from mice by plating mitomycin Ctreated lymphoid cells as infectious centers onto mink lung (ATCC CCL-64) or SC-1 (16) cells as described previously (9). The viruses were adapted to cell-free passage in mink lung cell cultures and were carried through two cycles of limiting dilution purification.…”
Section: Methodsmentioning
confidence: 99%
“…Xenotropic and wild mouse amphotropic viruses were titrated on mink S+L -cells (19). MCF viruses were quantitated by focus-formation in mink lung cells (9). NT, not tested.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it was found that response to CT26, MC38, A20 and NS1 was significantly higher that that observed for P815 or 18Neo ( p Ͻ 0.05). Because the MuLV gp70 env transcript is expressed in a variety of tumor cells and has been described as a tumor Ag (18,(25)(26)(27), we tested the presence of gp70 RNA transcripts in the different cell lines by RT-PCR. As shown in Fig.…”
Section: Cd4 ϩ Cells Induced In the Absence Of Cd25 ϩ And Cd8 ϩ Cellmentioning
confidence: 99%
“…Although the AKR/J strain has the predisposition to develop the disease since birth [4], the mean latent period is delayed until the age of 8 months. The long latent period has been attributed to the delayed formation of the leukemogenic dual tropic virus (DTV) with the MCF characteristic [5,6], formed in the thymus as a consequence of recombination within the envelope gene of ecotropic and xenotropic murine leukemia virus (MuLV). DTVs are detected only in preleukemic thymus and leukemic tissues of strains of mice prone to develop high incidence of leukemia [7].…”
mentioning
confidence: 99%